Peinture Contemporaine - Ragon, Michel (Tournai : Casterman, 1974)
Agam, Yaacov ; Atlan, Jean-Michel ; Bacon, Francis ; Balthus ; Bazaine, Jean ; Bissière, Roger ; Borduas, Paul-Émile ; Bryen, Camille ; Buffet, Bernard ; Dewasne, Jean ; Dubuffet, Jean ; Duvillier ; Estève, Maurice ; Fautrier, Jean ; Feito, Luis ; Fontana, Lucio ; Francis, Sam ; Gorky, Arshile ; Guitet, James ; Hartung, Hans ; Hélion, Jean ; Herbin, Auguste ; Johns, Jasper ; Klein, Yves ; Kline, Franz ; Koenig, John-Franklin ; Lapicque, Charles ; Lichtenstein, Roy ; Lurçat, Jean ; Magnelli, Alberto ; Manessier, Alfred ; Mathieu, Georges ; Matta, Sebastian ; Messagier, Jean ; Motherwell, Robert ; Pignon, Edouard ; Poliakoff, Serge ; Pollock, Jackson ; Rauschenberg, Robert ; Rebeyrolle, Paul ; Riopelle, Jean-Paul ; Rosenquist, James ; Rothko, Mark ; Schneider, Gérard ; Soulages, Pierre ; de Staël, Nicolas ; Tal Coat ; Tàpies ; Tobey, Mark ; Ubac, Raoul ; Vasarely ; Vieira da Silva ; Warhol, Andy ; Wols ; Zao Wou-Ki
Frans
boek